Characterization of forsythoside A metabolites in rats by a combination of UHPLC‐LTQ‐Orbitrap mass spectrometer with multiple data processing techniques. (23rd January 2018) - Wang, Fei; Cao, Guang‐shang; Li, Yun; Xu, Lu‐lu; Wang, Zhi‐bin; Liu, Ying; Lu, Jian‐qiu; Zhang, Jia‐yu
Abstract: Forsythoside A (FTA), the main active constituent isolated from Fructus Forsythiae, has various biological functions including anti‐oxidant, anti‐viral and anti‐microbial activities. However, while research on FTA has been mainly focused on the treatment of diseases on a material basis, FTA metabolites in vivo have not been comprehensively evaluated. Here, a rapid and sensitive method using a UHPLC‐LTQ‐Orbitrap mass spectrometer with multiple data processing techniques including high‐resolution extracted ion chromatograms, multiple mass defect filters and diagnostic product ions was developed for the screening and identification of FTA metabolites in rats. As the result, a total of 43 metabolites were identified in biological samples including 42 metabolites in urine, 22 metabolites in plasma and 15 metabolites in feces. These results demonstrated that FTA underwent a series of in vivo metabolic reactions including methylation, dimethylation, sulfation, glucuronidation, diglucuronidation, cysteine conjugation and their composite reactions. The research enhanced our understanding of FTA metabolism and built a foundation for further toxicity and safety studies.